Sex-Specific Relationships Between Interoceptive Accuracy and Emotion Regulation - Lischke, Alexander; Pahnke, Rike; Mau-Moeller, Anett; Jacksteit, Robert; Weippert, Matthias (Frontiers in Behavioral Neuroscience, 2020)
Over the last years, there has been a resurge in the interest to study the relationship between interoception and emotion. By now, it is well established that interoception contributes to the experience of emotions. However, it may also be possible that interoception contributes to the regulation of emotions. To test this possibility, we studied the relationship between interoception and emotion regulation in sample of healthy individuals (n = 84). We used a similar heartbeat detection task and a similar self-report questionnaire for the assessment of interoceptive accuracy and emotion regulation as in previous studies. In contrast to previous studies, we differentiated between male and female individuals in our analyses and controlled our analyses for individual characteristics that may affect the relationship between interoceptive accuracy and emotion regulation. We found sex-differences in interoceptive accuracy and emotion regulation that amounted to a sex-specific relationship between interoceptive accuracy and emotion regulation: Whereas interoceptive accuracy was related to reappraisal but not to suppression in male individuals, interoceptive accuracy was unrelated to reappraisal and suppression in female individuals. These findings indicate that the relationship between interoception and emotion regulation is far more complex than has been suggested by previous findings. However, these findings nonetheless support the view that interoception is essential for both, the regulation and experience of emotions.